Peningkatan Motivasi dan Hasil Belajar Bahasa Indonesia Melalui Model Problem Based Learning Kelas V SDN 08/II Rantau Duku - Ullia, Raudatul; Aprizan, Aprizan; Hidayat, Puput Wahyu (CV. Master Literasi Indonesia, 2025)
This study aims to describe the implementation of the Problem-Based Learning model in improving learning motivation, learning process, and learning outcomes of 20 fifth-grade students at SDN 08/II Rantau Duku. This type of research is Classroom Action Research (PTK) conducted in two cycles. The research instruments included questionnaires, teacher and student observation sheets, and learning outcome tests. Data analysis used a descriptive approach with qualitative and quantitative methods. The research success indicators were determined as follows: (1) at least 8% of students achieving a